2020
DOI: 10.1038/s41598-020-72230-0
|View full text |Cite
|
Sign up to set email alerts
|

Copaifera spp. oleoresins impair Toxoplasma gondii infection in both human trophoblastic cells and human placental explants

Abstract: The combination of pyrimethamine and sulfadiazine is the standard care in cases of congenital toxoplasmosis. However, therapy with these drugs is associated with severe and sometimes life-threatening side effects. The investigation of phytotherapeutic alternatives to treat parasitic diseases without acute toxicity is essential for the advancement of current therapeutic practices. The present study investigates the antiparasitic effects of oleoresins from different species of Copaifera genus against T. gondii. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 93 publications
2
26
0
Order By: Relevance
“…In this sense, combining our findings with literature, we hypothesized that the reduction in TNF-α levels, as result of COX-2 inhibition, may culminate in a decrease of PGE 2 production by infected villous, which could explain the impairment of the parasite growth. Taken together, in agreement with published studies, our data reveal a different cytokine profile between human trophoblast cells and villous explants from human third trimester pregnancy in the context of T. gondii 56 , 57 , 60 . In this context, we suggested that these differences among both models may be explained, in part, due to the fact that human villous is a tissue composed of mesenchyme, villous and extravillous trophoblast and syncytiotrophoblast, culminating in a distinct cytokine production.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this sense, combining our findings with literature, we hypothesized that the reduction in TNF-α levels, as result of COX-2 inhibition, may culminate in a decrease of PGE 2 production by infected villous, which could explain the impairment of the parasite growth. Taken together, in agreement with published studies, our data reveal a different cytokine profile between human trophoblast cells and villous explants from human third trimester pregnancy in the context of T. gondii 56 , 57 , 60 . In this context, we suggested that these differences among both models may be explained, in part, due to the fact that human villous is a tissue composed of mesenchyme, villous and extravillous trophoblast and syncytiotrophoblast, culminating in a distinct cytokine production.…”
Section: Discussionsupporting
confidence: 93%
“…Additonally, BeWo cells and HTR-8/SVneo showed below detection levels of IL-8, TGF-β1, and TNF, or IL-8, TNF and IL-10, respectively. Regarding to T. gondii infection in experimental models of maternal–fetal interface, previous studies also have reported, by ELISA assay, undetectable levels of TGF-β1, IL-12p70, TNF-α, and IFN-γ cytokines produced by BeWo cells, even after parasite infection 56 , 57 . In addition, a weak expression of IL-8 is commonly observed in unstimulated BeWo cells 72 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations